Evaluation of the toxic potential of calcium carbide in the third instar larvae of transgenic Drosophila melanogaster (hsp70-lacZ)Bg9. (November 2015) - Danish, Mohd.; Fatima, Ambreen; Khanam, Saba; Jyoti, Smita; Rahul,; Ali, Fahad; Naz, Falaq; Siddique, Yasir Hasan
Graphical abstract: Highlights: Analysis of CaC2 by Inductively Coupled Plasma Atomic Emission Spectroscopy (ICPAES). Larvae were exposed to CaC2. CaC2 at 4, 8, 16 and 32 × 10 −3  g/ml was found to be toxic. Impurities of metals such as mercury, copper and aluminium were found. Abstract: In the present study the toxic potential of calcium carbide (CaC2 ) was studied on the third instar larvae of transgenic Drosophila melanogaster (hsp70-lacZ)Bg 9 . The third instar larvae were exposed to 2, 4, 8, 16 and 32 × 10 −3  g/ml of CaC2 in diet for 24 h. The results reveal that the dose 2 × 10 −3  g/ml was not toxic but the remaining doses showed a dose dependent significant increase in the hsp70 expression, β-galactosidase activity, tissue damage, oxidative stress markers (lipid peroxidation and protein carbonyl content), glutathione-S-transferase activity, expression of Caspase 3 and 9, apoptotic index and DNA damage (midgut cells). A significant reduction as compared to control group in total protein, glutathione content and acetylcholinesterase activity was also observed. The Inductively Coupled Plasma Atomic Emission Spectroscopy analysis (ICPAES) reveals the presence of copper, iron, sodium, aluminium, manganese, calcium, nickel and mercury. The toxic effects of CaC2 in the present study may be attributed to the impurities present in it.